Perceptions, misconceptions and review of a neurosurgery on-call service in a university teaching hospital. (3rd March 2016) - Gulsin, Gaurav Singh; Anichini, Giulio; Bhatt, Pragnesh
Abstract: Background No published guidelines exist for how receiving unit doctors should manage referrals. Feedback regarding the quality of neurosurgical referral handling in our hospital has, in the past, been poor. We designed a novel means to appraise specialist referral handling, such that service delivery could be improved. We also aimed to identify differences, if any, between doctor perceptions versus actual satisfaction with the on-call neurosurgery service in our centre.Methods We first distributed questionnaires to gauge doctors' perceptions of our neurosurgery on-call service ('Perceptions of Neurosurgery Service' or 'PONS' questionnaire). Next we distributed a novel quality-of-service questionnaire ('Neurosurgery Service Assessment Questionnaire' or 'NSAQ') to all referring doctors over the three-month period between 01 March 2014 and 01 June 2014.Results Of the 57 respondents to the PONS questionnaire, 47.3% perceived the neurosurgical referral service to be 'poor' (36.8%, n  = 21) or 'very poor' (10.5%, n  = 6). Next the NSAQ was sent via email to the referring doctor of each of the 502 referrals received in the study period. A total of 52 responses were received by referring doctors (response rate = 10.36%). Actual referral handling ratings were overwhelmingly positive; 82.7% rated the handling of their referral as 'good' (21.2%, n  = 11), 'very good' (32.7%, n  = 17) or 'excellent' (28.9%, n  = 15).Conclusions We describe a novel method for receiving units to appraise their referral services and demonstrate its usefulness in our tertiary neurosurgical unit. We also demonstrate that most referring doctors are satisfied with the handling of their neurosurgical referrals, despite perceptions to the contrary.